Newborn Midwifery Care for Mrs. "E" Infant with Moderate Asphyxia at Bungi Health Center - Ines Tasya Pricilia; Minarti; Wa Ode Nurul Mutia (International Journal of Multidisciplinary Learners, 2025)
Background: Neonatorum asphyxia is a condition in which the baby is unable to breathe spontaneously and regularly, leading to a decrease in oxygen levels (O2) and an increase in carbon dioxide (CO2), potentially resulting in a negative impact on later life. The purpose of this study is to manage moderate asphyxia, which is characterized by babies who cry strongly, do not have hypothermia, and have vital signs within normal limits at the Bungi Health Center, Baubau City. The subject of this study was a newborn, Mrs. "E", who had moderate asphyxia. The method used in this study is a case study approach with Varney’s seven-step management and SOAP documentation. The results obtained showed that the subjective data in Mrs. "E" babies after treatment of asphyxia were showing improvement, characterized by strong crying babies and active body movements. Objective data showed that vital signs were within normal limits and the baby was already breastfed. The analysis carried out indicated improvement in Mrs. "E’s" baby who had moderate asphyxia problems. The management carried out includes warming, position adjustment, mucus suction, drying, and tactile stimulation, followed by an assessment known as HAIKAP. In conclusion, after carrying out midwifery care, moderate asphyxia has been resolved through tactile stimulation, showing success in the treatment provided. This research was conducted on February 19, 2024. The advice for practice places is to maintain services in accordance with the Standard Operating Procedures (SOP), especially in obstetric services for newborns with moderate asphyxia